RADIOGRAPHERS’ UTILISATION OF RADIOGRAPHIC CRITIQUE OF ROUTINE SHOULDER PROJECTIONS - Sebelego, Ida-Keshia (Bloemfontein: Central University of Technology, Free State, 2016)
Radiographers have a responsibility towards their patients to provide optimal patient care. Patient care involves, but is not limited to, positioning and applying radiation protection measures to ensure that optimal x-ray images are obtained (Brask & Birkelund, 2014:26). Optimal routine shoulder projections, namely, an anterioposterior (AP) projection (external rotation) and a lateral (LAT)-Y projection of the shoulder were investigated at the participating imaging department because it became evident to the researcher that the radiographers find it challenging to provide optimal routine shoulder images that adhere to specific radiographic criteria that contribute to patient care. The two research questions that were addressed for the research study were, (1) do radiographers and radiography students at the imaging department under investigation find it challenging to use/apply radiographic criteria to critique routine images of the shoulder, and (2) will a radiographic criteria checklist assist the researcher to determine the reasons for repeat shoulder routine projections at the participating imaging department? Therefore, the aim of the study was to determine the utilisation of radiographic criteria to evaluate the quality of routine shoulder images produced by the radiographers at the participating imaging department. A pragmatism paradigm was utilised for this research study. The research approach that was used in conjunction with the paradigm was mainly quantitative, with a few qualitative elements. A quantitative radiographic criteria checklist and quantitative radiographer critique questionnaire were compiled by the researcher with the assistance of literature to achieve the aim. Firstly, the researcher collected data utilising the radiographic criteria checklist that was pilot tested to evaluate 578 routine shoulder images obtained by student, qualified, community service and supplementary radiographers. The purpose of the radiographic criteria checklist was to determine the causes contributing to images not meeting the radiographic criteria and, therefore, the reasons for repeating routine shoulder projections. A simple/proportional random sampling technique was utilised to select the routine shoulder projections for evaluation on the display monitors. Raw/static routine shoulder images on the display monitors were evaluated, because these images did not undergo post-processing. Secondly, a pilot tested radiographer critique questionnaire was utilised to determine the knowledge of the participants regarding the anatomy of the shoulder and the way the routine shoulder images are evaluated for optimal positioning and exposure factor selection. A group-administered survey was utilised. All the participants gathered as a group and answered the radiographer critique questionnaire individually. This method contributed to the trustworthiness of this research study, by preventing the participants discussing the answers with each other. The researcher organised three sessions for participants to complete the radiographer critique questionnaire. The researcher converted the radiographer critique questionnaire into a clicker session to support the Go Green initiative and limiting printing. A total population sampling method was utilised for the participating radiographers because there was a small population at the participating imaging department, therefore, the whole population working at the participating imaging department could be included in the study. The questions were designed specifically to obtain information on how radiographers critique shoulder images and how they perform their radiographic technique to obtain projections of the shoulder. The radiographic criteria checklist shown that 89% of AP (external rotation) shoulder images and 73% of LAT-Y shoulder images had the incorrect centring point. Therefore 53% of the AP (external rotation) and 52% of the LAT-Y images did not demonstrate four-sided collimation. Utilising the incorrect centring point and not applying collimation effectively resulted in unnecessary exposed anatomical structures to radiation. Furthermore, the radiographers placed digital lead markers after an exposure was made for 34% of AP (external rotation) shoulder images and 39% of LAT-Y shoulder images. This practice is unethical and can have medico-legal complications. Ninety-four percent (94%) of AP (external rotation) projections and 71% of LAT-Y shoulder projections were repeated once due to positioning as the common reason for the repeats. There were significant differences in percentages for the radiographer critique questionnaire between radiographers and students in relation to identifying anatomical structures of the shoulder. The Fisher’s exact test was utilised to determine the significance (p-values). Moreover, there was a significant difference (p= 0.0076) among radiographers and students in identifying an AP (external rotation) shoulder image with optimal mAs. In addition, 85% of students and 71% of radiographers indicated that the AP (external rotation) image is positioned incorrectly (p= 0.4105), but only 56% of students and 50% of radiographers knew how to correct the shoulder image (p= 0.5800). Furthermore, 74% of students and 86% of radiographers could clearly identify a LAT-Y shoulder image that did not demonstrate correct positioning (p= 0.6925), but only 45% of students and 43% of radiographers could identify what corrective measures to obtain to ensure correct positioning (p= 0.7839). No significant difference in percentages between the radiographers and students were observed, however, a gap between practical application and theoretical knowledge has been clearly identified in this research study. The findings of the research study contributed significantly to identifying the contributing factors that lead to non-optimal shoulder images. Recommendations were made to address the factors contributing to non-optimal shoulder images to enhance optimal diagnostic imaging of the shoulder, which can contribute to an improvement in patient care at the participating imaging department.
Published Thesis
Keywords: routine shoulder projections; evaluation of image; optimal image; radiographic criteria checklist; radiographer critique questionnaire